Implementasi Prinsip Diskresi dalam Tugas Satpol PP Terhadap Penertiban Pedagang Kaki Lima - Muhammad Zulkifli; Rizki Tri Anugrah Bhakti; Indra Sakti; Seftia Azrianti (GUYUB: Journal of Community Engagement, 2026)
The enforcement of regulations against street vendors by the Civil Service Police Unit (Satpol PP) often creates a dilemma between maintaining public order and protecting the livelihoods of informal-sector communities. This condition highlights the need to strengthen the capacity of Satpol PP personnel in exercising administrative discretion in accordance with the General Principles of Good Governance (AUPB). This community service program aimed to enhance the knowledge and practical capacity of Satpol PP personnel in Batam City to implement discretionary authority in a lawful, proportionate, accountable, and public-oriented manner. The program was conducted through problem identification based on document review and case studies of street vendor enforcement, followed by educational sessions, focus group discussions (FGDs), and mentoring activities to evaluate enforcement practices using five indicators of good governance: legality, conformity with the purpose of authority, administrative prudence, proportionality, and public benefit. The results showed that the participants had a better understanding of the legal basis for administrative discretion; however, several challenges remained, including inconsistent administrative documentation, inadequate justification of discretionary decisions, and limited integration between enforcement measures and street vendor empowerment programs. In addition, the discussions revealed that enforcement actions focusing solely on restoring public order had not yet produced sustainable compliance and continued to generate social tensions with informal-sector vendors. The program recommends strengthening AUPB-based standard operating procedures, improving administrative documentation, enhancing pre-enforcement communication, and integrating enforcement activities with more comprehensive street vendor management and empowerment programs to ensure that the exercise of administrative discretion becomes more accountable, humane, and socially just.